2009
DOI: 10.1007/s00244-009-9325-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Organochlorine Pesticide Levels in Human Adipose Tissue of Inhabitants from Veracruz and Puebla, Mexico

Abstract: Since the discovery of insecticide properties of DDT (1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane) and HCH (hexachlorocyclohexane), they have provided great benefits to humans in sanitary actions to combat the spread of infection-borne disease vectors. Public Health Programs in Mexico used DDT and HCH until 1999 as the insecticides of choice to control disease-transmitting organisms. Because of their persistence and accumulative properties, organochlorine pesticides bioconcentrate in lipids of the human body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…Comparison of HCB, DDE, and DDT data from our cohort of five noncancer participants with those of the general population in Belgium (Covaci et al, 2002), however, do not show major differences. Recently published data from background populations in Mexico (Herrero-Mercado et al, 2010;Waliszewski et al, 2010) and Turkey (Daglioglu et al, 2010), however, show higher values for these countries compared with our data. These higher values are understandable given that phasing out of OCPs in Mexico and Turkey did not occur as early as in the USA and legal enforcement on the ban of these chemicals may not be as stringent in some jurisdictions compared with America.…”
Section: Resultscontrasting
confidence: 83%
“…Comparison of HCB, DDE, and DDT data from our cohort of five noncancer participants with those of the general population in Belgium (Covaci et al, 2002), however, do not show major differences. Recently published data from background populations in Mexico (Herrero-Mercado et al, 2010;Waliszewski et al, 2010) and Turkey (Daglioglu et al, 2010), however, show higher values for these countries compared with our data. These higher values are understandable given that phasing out of OCPs in Mexico and Turkey did not occur as early as in the USA and legal enforcement on the ban of these chemicals may not be as stringent in some jurisdictions compared with America.…”
Section: Resultscontrasting
confidence: 83%
“…The overall mean concentrations of PCBs in the Iraqi human adipose tissue samples were within the range of other results reported for different countries (USA/NY, Brazil, Belgium, Singapore, Korea, Japan, Italy and the Czech Republic) (Cok et al, 2010;Johnson-Restrepo et al, 2005;Kunisue et al, 2007;Moon et al, 2012;Pulkrabova et al, 2009;Schiavone et al, 2010;Tan et al, 2008;Waliszewski et al, 2010). In Italy, the total concentrations of PCBs were very high because of manufacturing these compounds till now, for example in Caffaro Company.…”
Section: Concentration Ofsupporting
confidence: 85%
“…Their harmfulness has been demonstrated by previous studies, such as the deleterious effect of DDT‐related compounds on Lake Apoka (in Florida) alligators (Guillette et al,1994). Also, the exposure to pesticides evidenced by storage of related residues in human tissues and excretion in urine (Garry et al,2001; Yucra et al,2008; Waliszewski et al,2010) were demonstrated to be associated with immune suppression, hormone disruption, cancer, and reproductive abnormalities (Abhilash and Singh,2009). Their pathological processes in the male reproductive system are triggered via endocrine disrupting (estrogenic, antiandrogenic, or antiestrogenic) effect (Garry et al,2001; Kamijima et al,2004; Lu et al,2004; Dallegrave et al,2007).…”
Section: Introductionmentioning
confidence: 99%